2022
DOI: 10.1007/s11739-022-02929-7
|View full text |Cite
|
Sign up to set email alerts
|

Renin–angiotensin system modulation and outcomes in patients hospitalized for interstitial SARS-CoV2 pneumonia: a cohort study

Abstract: Aim The role of cardiovascular (CV) pharmacotherapies in patients with severe COVID-19 pneumonia remains controversial. This study aims to assess the impact of renin-angiotensin system modulation (RASi) (either angiotensin-converting enzymes (ACEIs) or angiotensin-receptor blockers (ARBs)) on COVID-19 outcome. Methods We performed a cohort study on consecutive patients admitted for COVID-19 pneumonia at the Internal Medicine Unit of Sant'Orsola-Malpighi Hospital in Bologna, Italy. Patients with a possible alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…As in the case of other drugs, the potential beneficial effects of ARBs and ACEIs can be different in different patients depending on other external factors, including combinations with other treatments, patient comorbidities, and even the sex or age of the patient. In fact, beneficial effects were more clearly observed in studies that considered possible confounding factors and relevant bias in their analysis [ 31 , 136 ]. Obviously, the classical limitations of these drugs, such as the risk of potential birth defects in women that may get pregnant, must also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of other drugs, the potential beneficial effects of ARBs and ACEIs can be different in different patients depending on other external factors, including combinations with other treatments, patient comorbidities, and even the sex or age of the patient. In fact, beneficial effects were more clearly observed in studies that considered possible confounding factors and relevant bias in their analysis [ 31 , 136 ]. Obviously, the classical limitations of these drugs, such as the risk of potential birth defects in women that may get pregnant, must also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the possible beneficial or detrimental effects of therapies with ARBs and ACE inhibitors were highly controversial [ 45 , 46 ]. Research [ 47 , 48 ] and clinical studies [ 49 , 50 ] showed the non-detrimental and possible beneficial effects of these drugs. This has been detailed in our recent review article [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42][43] Fewer studies have been carried out in a single region or Hospital Center, [44][45] or have examined only some peculiar aspects concerning the impact of viral infection in human pathology. [46][47][48][49] On the other hand, while welldesigned multicenter studies allow for an improvement in the quality of the results obtained, the data collected may be heterogeneous and do not exactly reflect the characteristics, the clinical course and the prognosis of patients with COVID-19 belonging to narrower geographical areas. To date, few trials have investigated the trend of all these factors in patients with COVID-19, who have been admitted to the Internal Medicine/Cardiology Wards (IM/CW) in single Italian regions.…”
Section: Introductionmentioning
confidence: 99%